SIMPANAN MUDHARABAH BANK SYARIAH MANDIRI: STUDI KASUS 2011-2015 - Arini Mafarikhal Jannah (Jurusan Ilmu Ekonomi Prodi Ekonomi Pembangunan Fakultas Bisnis dan Ekonomika Universitas Surabaya, 2018)
Mudharabah is known as a contract or agreement and so the money used by amil (employers) in trade, then the profitis shared between them according to the terms stipulated in advance either evenly or with an excess of one over the other. Interest in mudharabah is no partnership effort between owner of the property (capital) that there is no experience in commercial or corporate or no opportunity to try themselves in the fieldof commerce, industry and so on with people experienced in the fieldbut did not have the capital. This study use a quantitative approach and methods of ordinary least square (OLS). In this study using fiveindependent variables and one dependent variable. The independent variables used in this study include its benchmark interest rate, profitsharing, Inflation,Bank Size and Promotion cost while the dependent variable is the mudharabah deposits. This study used a sample of Bank Syariah Mandiri branch Jemur Handayani, Surabaya with monthly data 2011-2015 period. The results of the analysis of all fiv variable indicates that the benchmark rate has a positive effect and insignificant,the results of profitsharing have a significantnegative effect, inflationhas a negative and insignificantimpact, the size of the banks has a positive and significantimpact, cost of sale has a positive and significantimpact affect the mudharabah deposits in Mandiri Syariah Bank branch office Jemur Handayani, Surabaya periode 201-2015.